2017
DOI: 10.1002/ejsp.2299
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identification, discrimination, and mental and physical health among Syrian refugees: The moderating role of identity needs

Abstract: Using a risk and resilience framework and motivated identity construction theory, we investigated the moderating role of identity needs in the association between social identification and perceived discrimination with mental and physical health among a sample of Syrian refugees (N = 361) in Turkey. Results showed that there were two clusters of interrelated identity needs, namely, belonging (belonging, continuity, and esteem) and efficacy (efficacy, meaningfulness, and distinctiveness). Higher perceived ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 56 publications
5
39
0
2
Order By: Relevance
“…Previous research has shown that discrimination could either undermine or promote individuals’ self‐esteem, depending on whether it threatens their worldview (Major, Kaiser, O'Brien, & McCoy, ). Thus, perceptions of individual‐level discrimination that counter adolescents’ worldview that the larger American society is not Islamophobic may undermine their self‐esteem and decrease their belongingness to the more powerful host‐national group because it does not satisfy their social identity need to belong to this group (Celebi, Verkuyten, & Bagci, ; Vignoles, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that discrimination could either undermine or promote individuals’ self‐esteem, depending on whether it threatens their worldview (Major, Kaiser, O'Brien, & McCoy, ). Thus, perceptions of individual‐level discrimination that counter adolescents’ worldview that the larger American society is not Islamophobic may undermine their self‐esteem and decrease their belongingness to the more powerful host‐national group because it does not satisfy their social identity need to belong to this group (Celebi, Verkuyten, & Bagci, ; Vignoles, ).…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off point of 1.75 became accepted in refugee settings and in cross-cultural research [ 49 , 50 ]; a cutoff of 2.0 has been suggested in research on Afghani patients attending primary health care facilities [ 51 ]. The Arabic version of the HSCL-25 used here has been found to be reliable and valid among Syrian refugees [ 17 , 52 ]. The current sample’s mean of 2.64 indicates that on average participants were experiencing clinically significant levels of anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, it considers (a) individual differences in self-regulation (i.e., regulatory focus; [ 16 ]) as an antecedent of coping and mental wellbeing and (b) contextual influences by investigating their relations among Syrian refugees in Turkey and Germany–countries that provide a shelter to a large number of refugees, but differ not only in terms of support structures and perspectives, but also in their proximity to the conflict zone. As such, it is one of very few social psychological investigations among this highly vulnerable population [ 17 ] and aims to make a modest contribution to this urgent problem.…”
Section: Introductionmentioning
confidence: 99%
“…Miller [30] suggests that interventions ought to be delivered through ecological frameworks that consider relationships between people and the settings they live in, the identification of naturally occurring resources within communities that can promote healing and healthy adaptation, and enhancement of coping strategies, for example, strengthening co-ethnic ties. Shared ethnic identity is protective when it provides psychological benefits such as a sense of belonging and continuity for refugees, as demonstrated in a recent study of Syrian refugees resettled in Turkey, which showed that strong ethnic identity moderates the effects of depression, PTSD and discrimination [31]. The protective effects of co-ethnic ties are further exemplified in our recent quantitative survey of Afghans in Turkey where we found that Afghans who reported having family and relatives in Turkey were more likely to seek professional health services, which we attributed to established Afghans' knowledge of navigating local health clinics [15].…”
Section: Discussionmentioning
confidence: 97%